The Relationship between Self-Control and Fear of Missing Out with Phubbing Behavior in Adolescents - Sugiharto, Jessica Rahardja; Suroso, Suroso; Pratitis, Niken Titi (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to determine the relationship between self-control and fear of missing out with phubbing behavior in adolescents. Phubbing is the behavior of ignoring the surrounding environment because they are more focused on their gadgets than establishing social interactions. Self-control is an individual's ability to manage themselves which is characterized by the ability to think (cognitive), act (behavior) and decide something according to their values, norms and beliefs. Fear of missing out is the fear of missing precious moments with friends or peer groups if the individual does not participate. The research method used is quantitative correlational with a sample of 139 adolescents aged 12-15 years. The data collection instrument used a phubbing scale, a self-control scale and a fear of missing out scale which were measured using a Likert scale. Data analysis was carried out using validity, reliability and multiple regression analysis tests. Based on the results of the analysis, it showed that the simultaneous correlation value F = 52.579 with a significance of 0.00 (p <0.05), meaning that there is a relationship between self-control and fear of missing out with phubbing in adolescents. Next, the partial correlation value between self-control and phubbing has a coefficient of t = -1.183 with a significance of 0.239 (p>0.05). The results show that although there is a tendency towards a negative relationship, this relationship is not statistically strong enough. The partial correlation between fear of missing out and phubbing has a coefficient of t = 7.067 with a significance of 0.000 (p<0.05), which means that there is a positive relationship between fear of missing out and phubbing in adolescents. The effective contribution given is 0.436. This means that self-control and fear of missing out have an influence of 43.6% on adolescent phubbing.